EXPLORING ESP COURSE: INSIGHTS FROM TEACHERS AND STUDENTS - Khairunnisa Dwinalida (JELLT (Journal of English Language and Language Teaching), 2023)
In the secondary school setting in Indonesia, English for Special Purposes (ESP) is taught in vocational schools. The competence of the results, however, falls short of what the workplace requires and expects. It suggests that there is a problem with the ESP-based teaching and learning process. This study attempts to find out how students and teachers perceive the ESP course at a vocational high school. 34 respondents in total, including 32 students and 2 English teachers, took part in the survey. Students were given a set of questionnaires with 34 closed-ended questions and 4 open-ended questions to help gain the information. Teachers were also interviewed to better understand their perspectives. The findings show that students' English proficiency is lacking, as indicated by students and teachers. Students are aware of the significance, challenges, and demands they will have in the future with regard to the ESP program. Teachers and students both agree that the focus of English learning materials should be on what employers want in the workplace. Finally, a number of possible problems with the ESP program are raised, including the length of instruction, the nature of the ESP, and the qualifications of the teachers. The findings of this study suggested that a collaborative approach to teaching might be an alternative to the current ESP curriculum in order to partially address the issue. Keywords: ESP program, teachers’ perception, students’ perception